Assessment Of Factors Influencing The Development Of International Event Tourism In The Russian Federation - Stytsiuk Rita Yurevna, Lustina Tatyana Nikolaevna, Artemyeva Olga Alexandrovna, Levchenko Konstantin Vladimirovich, Dubanevich Lyudmila Eduardovna (International Journal of Advanced Science and Technology, 2020)
The relevance of the problem under study is due to insufficient coverage of various aspects of the development of international event tourism, in particular the assessment of the impact of event tourism on the development of the territory. Purpose of the research is to identify factors that impede the development of event tourism in the constituent entities of the Russian Federation - this is based on the systematization of existing approaches and methods for a comprehensive assessment of the impact of event tourism on the development of the territory - and to develop proposals for building a factor model for assessing tourist flow.The leading research methods for this problem are the dialectic methods and the method of comparative typological analysis, the elements of the structural-functional approach, the conceptual modeling method, the systematic approach and the general scientific methods of cognition: analysis and synthesis, the unity of the logical and historical, from abstract to concrete. These methods allowed us to consider event tourism as an integral social, economic and geopolitical problem.